How glaucoma patient characteristics, self‐efficacy and patient–provider communication are associated with eye drop technique. (25th August 2015) - Sayner, Robyn; Carpenter, Delesha M; Robin, Alan L; Blalock, Susan J; Muir, Kelly W; Vitko, Michelle; Hartnett, Mary Elizabeth; Lawrence, Scott D; Giangiacomo, Annette L; Tudor, Gail; Goldsmith, Jason A; Sleath, Betsy
Abstract: Objectives: The objective of this study was to examine the extent to which patient characteristics, eye drop technique self‐efficacy, and ophthalmologist–patient communication about eye drop administration are associated with glaucoma patients' ability to instil a single drop, have the drop land in the eye, and avoid touching the applicator tip of the medication bottle to the eye or face while self‐administering eye drops. Methods: Glaucoma patients ( n  = 279) were recruited from six ophthalmology clinics. Medical visits were videotape‐recorded. Afterwards, patients were interviewed and demonstrated administering an eye drop on a videotaped‐recording. Generalized estimating equations were used to analyse the data. Key findings: Ophthalmologists provided eye drop administration instruction to 40 patients. Patients with more years of education were significantly more likely to both instil a single drop ( P  = 0.017) and have the drop land in their eye ( P  = 0.017). Women were significantly more likely to touch the applicator tip to their eyes or face ( P  = 0.014). Patients with severe glaucoma ( P  = 0.016), women ( P  = 0.026), and patients who asked at least one eye drop administration question ( P  = 0.001) were significantly less likely to instil a single drop. Patients with arthritis were significantly less likely to have the drop land in their eye ( P  = 0.008). African American patients were significantly less likely to touch the applicator tip to their eyes or face ( P  = 0.008). Conclusions: Some glaucoma patients have a difficult time self‐administering eye drops. As so few patients received eye drop administration instruction from their providers, there is an opportunity for pharmacists to complement care.